1991
DOI: 10.2190/kd3w-w2af-60k6-92h6
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Readability and Style of Letters to Stockholders

Abstract: One of the most effective communication links between corporate management and investors is the annual report. The letter to the shareholders in the report exemplifies the one-on-one communication attempt by chief executive officers and other high level executives with owners. This article examines thirty shareholder letters written by executives who are classified as highly successful based on their own annual salaries and/or the return to shareholders or company performance. The researchers found the letters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Advice on how to improve the readability and design of annual reports has come from Fielden and Dulek (1984), Haggie (1984), Anderson and Imperia (1992), and Arfin (1993). Dorrell and Darsey (1991) studied the readability of the annual letters to stockholders and found that they were understandable but often lacked a &dquo;you&dquo; attitude in writing style. Subramanian, Insley, and Blackwell (1993) reviewed the relationship between the performance of companies and the readability of their annual reports, finding that the annual reports of companies that performed well were easier to read than those of companies that did not perform well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Advice on how to improve the readability and design of annual reports has come from Fielden and Dulek (1984), Haggie (1984), Anderson and Imperia (1992), and Arfin (1993). Dorrell and Darsey (1991) studied the readability of the annual letters to stockholders and found that they were understandable but often lacked a &dquo;you&dquo; attitude in writing style. Subramanian, Insley, and Blackwell (1993) reviewed the relationship between the performance of companies and the readability of their annual reports, finding that the annual reports of companies that performed well were easier to read than those of companies that did not perform well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, to improve the readability of written material, the relationship between the difficulty experienced by users in reading a text and the characteristics of that text must be measured. Accordingly, readability indices have been developed to measure the effectiveness of written communication (Dorrell and Darsey ; Jones ). The better‐known indices are the Fog (Gunning , ; Kwolek ) and Flesch (Flesch , , ) Indices, which will be discussed in the research design and variable definitions section.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, researchers (Amernic et al, ; Palmer, King, & Kelleher, ) studied Jack Welch's CEO letters at General Electric over a 20‐year period to conclude that he applied five change conversations as well as distinct metaphors in his letters. Other researchers (Dorrell & Darsey, ; Patelli & Pedrini, ) considered the author's tone in leadership letters to conclude leaders predominantly write their letters with a positive tone, which increases corporate performance.…”
Section: Introductionmentioning
confidence: 99%